Oi cat! - Kes Gray (London; Hodder Children's Books, 2019)
According to Frog ... cats sit on gnats, dogs sit on logs, armadillos sit on pillows and chicks sit on bricks! But Cat doesn't like sitting on gnats. They keep biting his bottom. Will Frog help? Can Dog help? What else could Cat possibly sit on?
Keywords: picture books